2008
DOI: 10.1007/s10552-008-9140-y
|View full text |Cite
|
Sign up to set email alerts
|

Gynecological cancer survivors’ health behaviors and their associations with quality of life

Abstract: This research demonstrates the importance of integrating physical activity into follow-up of gynecological cancer survivors. Interventions to improve physical activity and test the causal effect of exercise on quality of life are a future research priority.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
5
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 32 publications
10
57
5
1
Order By: Relevance
“…5,6,11,14,29) Consistent with previous research, 27) presently women who met the criteria for PA showed better global QOL compared with those who did not. This finding suggests that PA is a key lifestyle behavior to improve global QOL in cancer survivors.…”
Section: 7)supporting
confidence: 83%
See 2 more Smart Citations
“…5,6,11,14,29) Consistent with previous research, 27) presently women who met the criteria for PA showed better global QOL compared with those who did not. This finding suggests that PA is a key lifestyle behavior to improve global QOL in cancer survivors.…”
Section: 7)supporting
confidence: 83%
“…This finding differs from findings in Western countries, where the 5-A-DAY recommendation was met in < 30% of cancer survivors. 11,14,15) Regarding diet quality, our participants also showed more positive results compared with two recent Western studies. The mean value of diet quality score was better (indicated by lower score) for our sample than in an earlier study 7) using the same instrument of DQI (4.6 versus 6.7, respectively).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Modifiable factors associated with HRQoL include obesity [26,27], lack of physical activity [20,[28][29][30], and psychosocial factors such as low social support [21,31]. The association between these factors and how they interact with one another warrants further research.…”
Section: Introductionmentioning
confidence: 99%
“…A cross-sectional mail survey from 802 gynecological cancer survivors evaluated health behaviors revealed no association between quality of life and fruit consumption, vegetable consumption, or BMI class [66]. In parallel to the selfreported survey study, an interventional lifestyle study of 27 ovarian cancer patients receiving chemotherapy treatment revealed minimal changes in fruit, vegetable, and low-fat dairy consumption--although this did not meet the recommended guidelines by the ACS [67].…”
Section: Interventionsmentioning
confidence: 91%